2015
DOI: 10.4103/0973-1482.157307
|View full text |Cite
|
Sign up to set email alerts
|

First experience of Candida non-albicans isolates with high antibiotic resistance pattern caused oropharyngeal candidiasis among cancer patients

Abstract: In conclusion, oropharyngeal Candidiasis is a serious infection among cancer patients. The isolated Candida spp. were resistant to common antifungal agents, which may lead to longer hospital stay, more expensive/toxic drugs and higher mortality. Therefore, interval surveillance is necessary in developing institutional guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Various authors have documented the prevalence of Candida in oral cancerous lesions ranging from 68% to 86%. [ 3 16 17 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various authors have documented the prevalence of Candida in oral cancerous lesions ranging from 68% to 86%. [ 3 16 17 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] Candida , though a commensal, can also cause oral mucosal infections in immunocompromised situations which are frequently seen in older individuals, infants, people infected with HIV, and individuals with cancer. [ 3 ] Colonization may lead to either a sustained or transient saprophytic association with the host or localized infections of mucosal surfaces. [ 2 ] There is significant association between histologically determined fungal infection of the oral mucosa and epithelial dysplasia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 4 5 ] There is a connection between epithelial dysplasia and histologically determined fungal infection of the oral mucosa. [ 6 ] It is suggested that Candida albicans tubular hyphal structure is needed because it allows for the entrance of precursors from saliva and the release of the nitrosamine agent into keratinocytes, possibly causing OSCC. [ 7 8 9 ] The ability of specific C. albicans strains to promote neoplastic transformation and the development of carcinogenic nitrosamines from saliva has revealed Candida's crucial role in malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Oral candidiasis is mostly treated with antifungal agents, some of which select for strains of Candida spp. resistant to such antimicrobial agents (173, 174). Therefore, there is a current need for preventive and therapeutic strategies for oral diseases that aim at restoring a healthy microbiome and increase its resistance to dysbiotic perturbations.…”
Section: Introductionmentioning
confidence: 99%